Salivary and serum interleukin 1 beta, interleukin 6 and tumor necrosis factor alpha in patients with leukoplakia and oral cancer - Brailo, V.; Vucicevic-Boras, V.; Lukac, J.; Biocina-Lukenda, D.; Alajbeg-Zilic, I.; Milenovic, A.; Balija, M. (Medicina oral, patología oral y cirugía bucal, 2012)
The aim of study was to compare salivary and serum concentrations of interleukin 1 beta (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) in patients with oral leukoplakia, oral cancer and healthy controls. Eighty eight patients (28 with oral cancer, 29 leukoplakia, and 31 healthy controls) were included in this study. Cytokine concentrations were measured by commercial enzyme linked immunoassay. Salivary IL-1β and IL-6 were significantly higher in oral cancer patients than in patients with leukoplakia and control group (p<0.05). No differences in concentrations of salivary TNF-α between either of the groups were observed. Serum concentrations of IL-1β were below level of detection in all but two participants. No significant differences between the groups were observed in serum concentrations of IL-6. Serum TNF-α was significantly higher in control subjects than in oral cancer patients. Patients with oral cancer have elevated levels of inflammatory cytokines in their saliva. Whether this elevation can be used for monitoring the malignant transformation of oral leukoplakia remains to be answered by further follow up studies.